TINJAUAN HUKUM TANGGUNG JAWAB MASKAPAI PENERBANGAN SIPIL TERHADAP KERUGIAN YANG TIMBUL BERDASARKAN KONVENSI CHICAGO TAHUN 1944 - Samuel B. Nababan; Sutiarnoto Sutiarnoto; Chairul Bariah (Journal of USU International Law, 2013)
ABSTRACT Unitary Republic of Indonesia is an archipelago with inter-island intensity is high enough, so that the necessary protection against the user maximum facility cost consumers in this regard. In this study, the economic aspects of the problem include regulation of civil aviation convention in chicago, 1944, setting the technical and operational aspects of the flight by civil convention in chicago in 1944 and a form of civilian airlines chicago convention in 1944. As for the type of study of this paper is normative research . Normative research is a study of the principles of law , systematic research on law and legal research on synchronization . With the aim to compare the Indonesian positive law governing the civil aviation in the Act 1 of 2009 on Flight to chicago Convention 1944 which is the benchmark of international law in the case of civil aviation . Data sources and collection techniques used in this study is a secondary data , which consists of primary legal materials in the form of legal products such as legislation , which in this case in the form of legislation , international law conventions , declarations , and protocols . Secondary legal materials such as reference materials sourced from books , newspapers , media, internet and other media related to the issues discussed . Tertiary legal materials in the form of materials that give instructions and explanations of the primary and secondary legal materials , such as dictionaries and so on . Results from this study is that the Chicago 1944 convention has been set explicitly linked to economic aspects and the technical aspects of the airline in order to minimize accidents and forms pertanggungjawaba n of the airline when the accident occurred is of course detrimental to the consumer . Keywords : Responsibility , Airlines , Losses .